The Influence Of Supervisor Academic Supervision And Teaching Experience On Educators' Pedagogic Competence - Sappaile, Baso Intang; Abeng, Andi Tenri; Nuridayanti, Nuridayanti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
The purpose of this study was to determine the effect of supervisors' academic supervision and teaching experience on the pedagogical competence of educators. The method used is a qualitative research method based on field research. The location of this research was at SMA Abdi Pembangunan Makassar and SMA Amanah Nusantara Makassa, and the participants in this study numbered two people each from these schools. The results of this study concluded that the influence of supervisors' academic supervision and teaching experience had an effect on educators' pedagogy. This is because at SMA Abdi Pembangunan Makassar and SMA Amanah Nusantara Makassar, it is shown that the supervisor's academic supervision and teaching experience have a positive effect on the pedagogical competence of educators. Effective academic supervision assists educators in developing teaching skills and increasing their understanding of effective learning approaches. Whereas broad and varied teaching experience allows educators to develop a better understanding of effective teaching strategies. The combination of good academic supervision and diverse teaching experiences can make a significant contribution to improving the pedagogical competence of educators in schools.